Math, asked by jasleen12345, 1 year ago

Solve this..Need urgently

Attachments:

Answers

Answered by JainAbhishek
2

SOLUTION:

a+(n-1)d=1/m...............(1)

a+(m-1)d=1/n..............(2)

subtract (2) from (1)

a+(n-1)d-a- (m-1)d=1/m-1/ m

d{n-m-1+1}=(n-m)/nm

d(n-m)=(n-m)/nm

d=1/nm

put value of d in equation (1) or (2)

we get a=1/ nm

then:

a(nm) th term =a+(mn-1)d=1/ mn+(mn-1)/nm

a(mn)=(1+mn-1)/nm=nm/nm=1

s(mn)= mn/2[2a+(mn-1)d]

on putting value of a & d then solving we get:

s(mn)= (mn-1)/2

Similar questions